Multi-Purpose Cooperatives’ Business Practices and Performance in Samarica, Occidental Mindoro - Sunga, Maria Angelica; G. Decena, Adrian (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study generally aims to determine the significant difference in the business practices and performance of multi-purpose cooperatives when grouped according to their profile. Also, it aims to determine the relationship between the business practices and performance of the MPCs. The result revealed that only the marketing Practices of MPCs from San Jose and Calintaan has significant differences; while, only the facilities management of San Jose and Magsaysay has shown significant difference. The findings also show that only the credit performance of the MPC from San Jose and Magsaysay; and, Production performance of Magsaysay and Calintaan have significant differences. The study has found that there is strong significant relationship between the business practices and performance of multi-purpose cooperatives in SAMARICA, Occidental Mindoro. The findings of the study are expected to contribute to both theory and practice.